PENGARUH BEBAN KERJA, LINGKUNGAN KERJA, DAN PROMOSI JABATAN TERHADAP KINERJA KARYAWAN PADA PT THAMRIN BROTHERS BATURAJA 1 - Rika Agustina; Novie Al Muhariah; Rr Dimas Veronica Priharti (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2024)
This research discussed the influence of workload (X1), work environment (X2), and position promotion (X3) on employees' performance (Y) at PT Thamrin Brothers Baturaja 1. The population in this study was all employees at PT Thamrin Brothers Baturaja 1 totaling 39 people. This research was quantitative research with the analytical method used, namely Multiple Linear Regression Analysis using Validity and Reliability Tests. The results of the analysis showed that the variables Workload, Work Environment and Position Promotion influenced employees' performance at PT Thamrin Brothers Baturaja 1 both partially and simultaneously. The coefficient of determination (Adjusted R Square) was obtained at 0.617. This showed that the contribution of the influence of Work Load (X1), Work Environment (X2), and Position Promotion (X3) to Employees' Performance (Y) at PT Thamrin Brothers Baturaja 1 was 61.7%, while the remaining 38.3% was influenced by Other variables not included in this research include work motivation, work discipline and leadership (Afandi, 2018:86).